When inflammation meets lung development—an update on the pathogenesis of bronchopulmonary dysplasia - Holzfurtner, Lena; Shahzad, Tayyab; Dong, Ying; Rekers, Lisa; Selting, Ariane; Staude, Birte; Lauer, Tina; Schmidt, Annesuse; Rivetti, Stefano; Zimmer, Klaus-Peter; Behnke, Judith; Bellusci, Saverio; et al. (Molecular and cellular pediatrics, 2022)
Even more than 50 years after its initial description, bronchopulmonary dysplasia (BPD) remains one of the most important and lifelong sequelae following premature birth. Tremendous efforts have been undertaken since then to reduce this ever-increasing disease burden but a therapeutic breakthrough preventing BPD is still not in sight. The inflammatory response provoked in the immature lung is a key driver of distorted lung development and impacts the formation of alveolar, mesenchymal, and vascular structures during a particularly vulnerable time-period. During the last 5 years, new scientific insights have led to an improved pathomechanistic understanding of BPD origins and disease drivers. Within the framework of current scientific progress, concepts involving disruption of the balance of key inflammatory and lung growth promoting pathways by various stimuli, take center stage. Still today, the number of efficient therapeutics available to prevent BPD is limited to a few, well-established pharmacological interventions including postnatal corticosteroids, early caffeine administration, and vitamin A. Recent advances in the clinical care of infants in the neonatal intensive care unit (NICU) have led to improvements in survival without a consistent reduction in the incidence of BPD. Our update provides latest insights from both preclinical models and clinical cohort studies and describes novel approaches to prevent BPD.